2014
DOI: 10.15580/gjbs.2014.2.012314056
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Root Distribution and Tensile Strength of Acacia mangium Willd (Fabaceae) in the Rainforest

Abstract: The purpose of this study is to complement the existing body of knowledge on the root system of tropical plants and their contribution to slope stability. For this reason, four trees of Acacia mangium selected as randomly in rainforest along East-West Highway, Malaysia. Root area ratio (RAR) and tensile strength (Tr) data were collected and analyzed. RAR data were measured with the whole root system and Tr were measured by individual roots. The results showed that there is a power law equation between root dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…Similarly, Naghdi et al [2] found that when plants vegetated on the entire slope, the FOS increased significantly than when vegetation grew only on the slope toe, slope surface, on the top of slope. On the contrary, Habibah et al, [10] stated that when a hillslope was vegetated with trees at the bottom of the slope, it became more effective in slope stabilization than at any other position on the slope. To investigate the contradictions between the previous studies, the spatial distribution of vegetation on the slope were conducted and compared among the selected plant species.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, Naghdi et al [2] found that when plants vegetated on the entire slope, the FOS increased significantly than when vegetation grew only on the slope toe, slope surface, on the top of slope. On the contrary, Habibah et al, [10] stated that when a hillslope was vegetated with trees at the bottom of the slope, it became more effective in slope stabilization than at any other position on the slope. To investigate the contradictions between the previous studies, the spatial distribution of vegetation on the slope were conducted and compared among the selected plant species.…”
Section: Introductionmentioning
confidence: 97%
“…The mechanism through which root-reinforced soil is related to concrete reinforcement mainly plays the role of shear stress and tensile strength effect. The effect of root reinforcement increases the cohesive strength of soil, decreases soil deformation, prevents the incidence of surface tension cracks, and can avoid slope failure initiated by triggering factors [6][7][8][9][10][11][12][13][14][15][16]. The shear stress is developed in the soil and transferred to the ground as tensile resistance in the roots, which ensures mechanical reinforcement by the roots [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…A grid of cells of 100 cm 2 was overlapped on each profile in order to obtain RAR data (red grid in Figure 5). For each cell, roots were counted and grouped into different diameter classes, then RAR i was calculated by using the following formula [12,42,60]:…”
Section: For Peer Review 8 Of 23mentioning
confidence: 99%
“…Naghdi et al (2013) stated that FoS was highest when the vegetation was on the entire slope. According to Habibah et al (2014), slope stabilization is more effective for vegetation planted at the foot than in other parts. The effect of vegetation on the top and surface slopes on the factor of safety is better than at the foot when the plant root system penetrates the solid soil (Fan and Lai, 2014).…”
Section: Root Cohesionmentioning
confidence: 99%
“…Root tensile strength is a fundamental mechanical characteristic for increasing soil reinforcement (Genet et al, 2007;Naghdi et al, 2013;Stokes et al, 2004). This is due to its performance in increasing soil cohesion, reducing its deformation, and preventing surface tension cracking (Habibah et al, 2014;Ishak et al, 2016;Temgoua et al, 2016). The shear stress formed in the soil is transferred as tensile resistance to ensure the effect of mechanical strengthening by roots (Bordoni et al, 2016;Gonzalez-Ollauri and Mickovski, 2017;Lateh et al, 2011;Schwarz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%